2013
DOI: 10.1556/achrom.25.2013.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and determination of trace alkaloids in seeds extracts fromPeganum harmalalinn. Using LC-ESI-MS and HPLC

Abstract: Summary. Harmaline and harmine accounted for more than 70% in composition in extracts of P. harmala. More attention, however, should be paid to the other alkaloids which would be favorable or unfavorable to the efficacy and safety of the products. It was necessary to determine these trace alkaloids in the extracts; thereafter, most of them have been characterized. Diglycoside vasicine, vasicine, vasicinone, harmalol, harmol, tetrahydroharmine, 8-hydroxy-harmine, ruine, harmaline, and harmine were separated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 19 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…The characteristic fragment ions were key to study and understand the fragmentation mechanisms and to support metabolite annotation with a higher confidence level (Figures 2 and 3). Besides they are in agreement with previous studies [22][23][24]. Results show that P. viridis, M. hostilis and Dc Ab are the ones that contain the highest levels of tryptamine alkaloids, mainly DMT and 5-OH-DMT [25].…”
Section: Characterization Of Alkaloid Derivatives and Other Compoundssupporting
confidence: 92%
“…The characteristic fragment ions were key to study and understand the fragmentation mechanisms and to support metabolite annotation with a higher confidence level (Figures 2 and 3). Besides they are in agreement with previous studies [22][23][24]. Results show that P. viridis, M. hostilis and Dc Ab are the ones that contain the highest levels of tryptamine alkaloids, mainly DMT and 5-OH-DMT [25].…”
Section: Characterization Of Alkaloid Derivatives and Other Compoundssupporting
confidence: 92%
“…The resulting collapse of the proton motrice force and depletion of the ATP pool lead to eventual cell death. Liu et al (2013) determined the main and trace alkaloids in the seed extracts of P. harmala using liquid chromatography-electrospray ionization-mass spectrometry (LC-ESI-MS) and high-performance liquid chromatography (HPLC).They found that Harmaline and harmine make more than 70% of the alkaloids. Diglycoside vasicine, vasicine, vasicinone, harmalol, harmol, tetrahydroharmine, 8-hydroxy-harmine, ruine, harmaline, and harmine were found to be the other alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of main active components alkaloids, the seeds of P. harmala are rich in β-carboline alkaloids harmine, harmane, and harmaline which showed to possess hallucinogenic effects (Araújo et al, 2015;Cheng et al, 2010) and are lacking in quinazoline alkaloids, namely, VAS, DVAS, and VAO. By contrast, APP mainly contain the quinazoline alkaloids (VAS, DVAS, and VAO) and contain only trace amounts of β-carboline alkaloids harmine, harmane, and harmaline (Cheng et al, 2010;Liu et al, 2013;Wang et al, 2002;Wen et al, 2014). The fact that APP contains only trace amounts of them, APP appears suitable for the development of an antitussive and expectorant phytomedicine in the future.…”
Section: Discussionmentioning
confidence: 99%